ANALISIS METODE PENDETEKSIAN FRAUD FINANCIAL STATEMENT: LITERATUR REVIEW - Johan Setiawan (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2021)
The purpose of this study is to determine the development, focus, and methodology of the financial statement fraud literature and how this research will develop in the future. This study uses a structured literature review (SLR) to study a collection of studies whose criteria have been determined. The type of data used is secondary data on fraud financial statements from 2016-2021. It can be seen that financial statement fraud is divided into 3 parts, namely fraud triangle theory (rationalization, motivation/need/pressure, and opportunity), fraud diamond theory (adds the ability value of the fraud triangle theory), and fraud pentagon theory (adds the arrogance value of the fraud triangle theory). fraud diamond theory). In this study, agency theory is most often associated with fraud financial statements and it can be seen that the measurement of fraud financial statements is most often used by the F-Score method, and the sectors that are most often studied are the manufacturing sector and the financial sector.